ANALISIS KANDUNGAN PROTEIN, LEMAK DAN KADAR AIR KEONG AIR TAWAR (Filopaludina javanica) DI SUNGAI WAUNG KECAMATAN GLAGAH KABUPATEN LAMONGAN - Ali Mahruf; Andi Rahmad Rahim; Aminin Aminin (Jurnal Perikanan Pantura (JPP), 2020)
Feed is an important thing for fish cultivators, apart from the nutritional content of the feed it is also seen in terms of price and availability. When fish are cultivated, feed becomes a limiting factor for production. Likewise with fish maintenance, it requires the availability of feed that is suitable in terms of size, nutrition, and quantity. The purpose of this study was to determine the levels of protein, fat, and water content in the freshwater snails (Filopaludina javanica) in the waters of the Waung River. In this study, it was taken from the Waung river which is located in Glagah District, Lamongan Regency, because the river is filled with freshwater snails. This research has 2 stages, namely descriptive and experimental research with sampling at 3 points waung river station. Snail samples were taken in living conditions and brought to the Laboratory of the Department of Marine Affairs and Fisheries, UPT, quality testing and development of marine and fishery products in Surabaya for laboratory tests. The conclusion that can be drawn from this research is that the freshwater snails in the Waung River, Glagah District, have the highest protein at station 2 in the middle of the river at 16.20%. The highest fat content was also obtained at station 2 in the middle of the river at 3.39%, while the highest water content was obtained at station 3 at the downstream of the river at 78.99%.